Omega‐3 fatty acids are associated with blood–brain barrier integrity in a healthy aging population. Issue 8 (29th July 2021) - Barnes, Samuel; Chowdhury, Shilpy; Gatto, Nicole M.; Fraser, Gary E.; Lee, Grace J.
Abstract: In aging populations, omega‐3 polyunsaturated fatty acids (PUFAs) have been associated with better cognitive function, slower rates of cognitive decline, and lower risk of developing dementia. Animal studies have shown that diets rich in omega‐3 PUFAs reduce blood–brain barrier (BBB) disruption associated with aging, but this has yet to be observed in humans. Forty‐five healthy subjects (mean age, 76 years) were recruited and underwent cognitive assessment (verbal learning and memory, language, processing speed, executive function, and motor control) and measurement of PUFAs. Forty of the same subjects also underwent magnetic resonance imaging (MRI) to measure BBB integrity ( K trans using dynamic contrast‐enhanced MRI). The long chain omega‐3 score (DHA+EPA) was negatively correlated with K trans values in the internal capsule, indicating higher omega‐3 levels were associated with greater BBB integrity in this region ( r = –0.525, p = .004). Trends were observed for a positive correlation between the long chain omega‐3 score and both memory and language scores, but not with executive function, speed, or motor control. The omega‐6 score was not significantly correlated with any cognitive scores or K trans values. The significant correlations between long chain omega‐3 levels and BBB integrity provide a possible mechanism by which omega‐3 PUFAs are associated with brain health. Abstract : This work measured cognition, blood‐brain barrier integrity, and long chain omega‐3 levels in 45 health older adults. We found significant correlations between long chain omega‐3 levels and BBB integrity, providing evidence of a possible mechanism by which omega‐3 may contribute to brain health.